2012
DOI: 10.1128/jvi.01958-12
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus Protein nsp1 Is a Novel Eukaryotic Translation Inhibitor That Represses Multiple Steps of Translation Initiation

Abstract: Severe acute respiratory syndrome (SARS) coronavirus nonstructural protein 1 (nsp1) binds to the 40S ribosomal subunit and inhibits translation, and it also induces a template-dependent endonucleolytic cleavage of host mRNAs. nsp1 inhibits the translation of cap-dependent and internal ribosome entry site (IRES)-driven mRNAs, including SARS coronavirus mRNAs, hepatitis C virus (HCV), and cricket paralysis virus (CrPV) IRES-driven mRNAs that are resistant to nsp1-induced RNA cleavage. We used an nsp1 mutant, nsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
303
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(320 citation statements)
references
References 40 publications
17
303
0
Order By: Relevance
“…A subsequent BCoV DI RNA mutagenesis study further suggested that this multipartite RNA structure may involve several stem-loop (sub)structures identified in earlier studies (Gustin et al, 2009;Raman and Brian, 2005) but require refolding of other RNA structures suggested earlier to be essential for DI RNA replication (Brown et al, 2007). The study by Su et al (2014) also identified an intriguing requirement in cis of an oligopeptide sequence in the Nproximal part of nsp1, suggesting that nsp1 may be an essential cis-acting protein factor in betacoronavirus replication, in addition to its multiple other functions (Brockway and Denison, 2005;Huang et al, 2011a,b;Kamitani et al, 2006Kamitani et al, , 2009Lei et al, 2013;Lokugamage et al, 2012;Narayanan et al, 2008a;Tanaka et al, 2012;Tohya et al, 2009;Wathelet et al, 2007;Züst et al, 2007). Possible interacting partners for nsp1 remain to be identified.…”
Section: Functional and Structural Features Of Coronavirus 5 Cis-actimentioning
confidence: 92%
“…A subsequent BCoV DI RNA mutagenesis study further suggested that this multipartite RNA structure may involve several stem-loop (sub)structures identified in earlier studies (Gustin et al, 2009;Raman and Brian, 2005) but require refolding of other RNA structures suggested earlier to be essential for DI RNA replication (Brown et al, 2007). The study by Su et al (2014) also identified an intriguing requirement in cis of an oligopeptide sequence in the Nproximal part of nsp1, suggesting that nsp1 may be an essential cis-acting protein factor in betacoronavirus replication, in addition to its multiple other functions (Brockway and Denison, 2005;Huang et al, 2011a,b;Kamitani et al, 2006Kamitani et al, , 2009Lei et al, 2013;Lokugamage et al, 2012;Narayanan et al, 2008a;Tanaka et al, 2012;Tohya et al, 2009;Wathelet et al, 2007;Züst et al, 2007). Possible interacting partners for nsp1 remain to be identified.…”
Section: Functional and Structural Features Of Coronavirus 5 Cis-actimentioning
confidence: 92%
“…Furthermore, a mutagenesis study using BCoV DI RNA indicated that this multipartite RNA structure may involve several SL substructures identified in earlier studies (Gustin et al, 2009;Raman and Brian, 2005) but require refolding of other RNA structures suggested earlier to be essential for DI RNA replication (Brown et al, 2007). A recent study provided evidence that a short oligopeptide from the N-terminal domain of nsp1 may be an essential cisacting protein factor involved in betacoronavirus replication, thus adding to the multiple other functions of this protein (Brockway and Denison, 2005;Huang et al, 2011a,b;Kamitani et al, 2006Kamitani et al, , 2009Lei et al, 2013;Lokugamage et al, 2012;Narayanan et al, 2008a;Tanaka et al, 2012;Tohya et al, 2009;Wathelet et al, 2007;Z€ ust et al, 2007).…”
Section: Functional Roles Of Coronavirus 5 0 -Terminal Cis-acting Elementioning
confidence: 93%
“…This region in which spike glycoprotein binds to ACE2 had 21 mutations not found in RaTG13, suggesting their role in the adaptation to human hosts. Peptide nsp1 facilitated viral gene expression and evasion from the host immune response [10]. Peptide nsp3, named papain-like proteinase, was found to be associated with the cleavages, viral replication, and antagonization of innate immune.…”
Section: Dear Editormentioning
confidence: 99%